Pelatihan Desain Konten Media Sosial untuk Meningkatkan Literasi Digital Tenaga Pendidik Yayasan Al-Hidayah - Nurul Chairany; Irma Nur Afiah; Muhammad Budi Adiputra; Moh Farouq (Pusat Riset dan Inovasi Nasional, 2026)
This Community Service Program aims to improve the digital literacy and competence of educators at the Al-Hidayah Foundation through training in the design of educational and communicative social media content. The main problem faced by the partner is the educators' limited understanding and skills in designing visual content, composing engaging narratives, and managing social media in a planned and consistent manner. This condition has caused the Foundation's use of social media to remain suboptimal as a means of information, education, and reinforcement of the institution's image. As a solution, this activity was designed as structured training covering an introduction to the role of social media in education, content design practice using easy-to-operate digital applications, and mentoring in developing content aligned with the identity and values of the Al-Hidayah Foundation. The activity was attended by 6 educators as training participants. The pre-test results showed an average participant knowledge score of 40, while the post-test results showed an increase to 87.7, equivalent to an improvement of 47.7%. This indicates that the training provided was effective in improving educators' understanding of social media literacy and content design. Through this activity, the educators are expected to be able to produce more creative, informative, and sustainable social media content, thereby supporting the improvement of digital communication quality and the institution's existence within the community.